Smoking Outcome Expectancies in Young Adult Female Smokers: Individual Differences and Associations with Nicotine Dependence in a Genetically-informative Sample - Kristjansson, Sean D. (2010)
Outcome expectancy is a central construct in models of addiction. Several outcome expectancies associated with smoking cigarettes have been identified, and studies suggest that individual differences in smoking expectancies are related to important aspects of tobacco use, including levels of smoking, nicotine dependence and smoking cessation. In the present study, we used a novel analytic method, exploratory structural equation modeling (ESEM), to quantify smoking expectancies from a subset of items adapted from the Smoking Consequences Questionnaire (SCQ; Brandon and Baker, 1991) and SCQ-Adult (Copeland et al., 1995). In our sample of 1262 monozygotic and dizygotic young adult, female twins who were regular smokers, we quantified six smoking expectancy factors similar to those reported in previous studies. These included Negative Affect Reduction, Boredom Reduction, Weight Control, Taste Manipulation, Craving/Addiction and Stimulation-State Enhancement. We used genetic model-fitting to examine the extent to which individual differences in the expectancies were influenced by latent genetic, shared environmental and non-shared environmental factors. We also examined the validity of the expectancy factors by examining their associations with nicotine dependence (ND) before and after adjusting for comorbid diagnoses of drug dependence and alcohol use disorder. Results of the validity analysis indicated that all of the expectancies were associated with ND after covariate adjustment. Although we lacked the statistical power to distinguish between genetic and shared environmental sources of variance, our results suggest that smoking outcome expectancies aggregate in families, but the majority of variance in these expectancies is due to environmental factors specific to the individual.